Barrier busting in energy efficiency in industry - Schleich, Joachim (UNIDO ViennaAT, 2011)
Gives a conceptual overview of barriers to energy efficiency at the macro and organisational levels, including a brief discussion of policy implications. Discusses the rationale for policy intervention thereby further distinguishing between barriers that may warrant policy intervention and those that may not.